ChemInform Abstract: Types, Principle, and Characteristics of Tandem High‐Resolution Mass Spectrometry and Its Applications. Issue 9 (February 2016) - Lin, Longfei; Lin, Hongmei; Zhang, Miao; Dong, Xiaoxv; Yin, Xingbin; Qu, Changhai; Ni, Jian
Abstract: Review: 132 refs.